2000
DOI: 10.1161/01.str.31.10.2500
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular pH, Ca 2+ Influx, and Response of Vascular Smooth Muscle Cells to 5-Hydroxytryptamine

Abstract: Background and Purpose-Cerebral vascular smooth muscle cells (VSMCs) contract on extracellular pH (pH o ) increases and relax on pH o decreases. These changes in tone are believed to result from changes in [Ca

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…The tissues in which opening of Cx43 HCs by extracellular alkalinization could play relevant roles are the biliary and intestinal epithelium, where Cx43 is expressed (5,25) and cells are exposed to pH values close to or above 8.0 (21,35). Ca 2ϩ influx via Cx43 HCs might also explain the alkalinizationinduced increase in intracellular [Ca 2ϩ ] through Ca 2ϩ influx in vascular endothelial and vascular smooth muscle cells (1,42,73). Moreover, Ca 2ϩ influx through Cx43 HCs could participate in a range of undesired effects of the hypocalcemia that results from alkalemia.…”
Section: Discussionmentioning
confidence: 99%
“…The tissues in which opening of Cx43 HCs by extracellular alkalinization could play relevant roles are the biliary and intestinal epithelium, where Cx43 is expressed (5,25) and cells are exposed to pH values close to or above 8.0 (21,35). Ca 2ϩ influx via Cx43 HCs might also explain the alkalinizationinduced increase in intracellular [Ca 2ϩ ] through Ca 2ϩ influx in vascular endothelial and vascular smooth muscle cells (1,42,73). Moreover, Ca 2ϩ influx through Cx43 HCs could participate in a range of undesired effects of the hypocalcemia that results from alkalemia.…”
Section: Discussionmentioning
confidence: 99%
“…Secondly, and much more plausible, are the alterations in pH resulting from changes in P aCO 2 . VSM studies in vitro have shown that changes in extracellular pH affect endothelial function and intracellular nitric oxide (Capellini et al 2013), as well as calcium influx, but not intracellular calcium release (Nazarov et al 2000). Of particular relevance, reducing pH also reduced the rate of VSM shortening in the rat portal vein (Peiper et al 1976), which would have a direct link to the reduced F upLim we found with hypercapnia.…”
Section: Physiological Considerationsmentioning
confidence: 66%
“…), as well as calcium influx, but not intracellular calcium release (Nazarov et al . ). Of particular relevance, reducing pH also reduced the rate of VSM shortening in the rat portal vein (Peiper et al .…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, agents acting directly on the vascular smooth muscle cell may alter tone by three mechanisms: altering intracellular Ca 2+ concentrations ([Ca 2+ ] i ), varying the sensitivity of the contractile regulatory apparatus to [Ca 2+ ] i or modulating the sensitivity to other vasoactive inputs [11] . In this context, EERMv (72 and 120 µg/mL) inhibited the concentration-response contraction of NE in a nonparallel manner and depressed the maximal response (Fig.…”
Section: Resultsmentioning
confidence: 99%